Efficient Synthesis of 3-Alkynyl-2-(hydroxymethyl)cyclohex-2-en-1-ones by a Stork–Danheiser Sequence from Vinylogous Esters and Terminal Alkynes - Parida, Amarchand; Sharique, Mohd.; Kakde, Badrinath N.; Ghosh, Santanu; Bisai, Alakesh (Synthesis, 2015)
An efficient Stork–Danheiser sequence has been developed for the preparation of a variety of 3-alkynyl-2-(hydroxymethyl)cyclohex-2-en-1-ones in good to excellent yields from the corresponding 4,6,7,8-tetrahydro-5H-1,3-benzodioxin-5-ones and terminal alkynes. Several of the 3-alkynyl-2-(hydroxymethyl)cyclohex-2-en-1-one products were catalytically cyclized to give the corresponding 3-aryl-1,5,6,7-tetrahydro-8H-isochromen-8-ones.
Keywords: alkynylations; Stork–Danheiser sequences; vinylogous esters; alkynes; cyclizations; chromenones